2017
DOI: 10.1016/j.jss.2017.02.069
|View full text |Cite
|
Sign up to set email alerts
|

Assessing written communication during interhospital transfers of emergency general surgery patients

Abstract: Background Poor communication causes fragmented care. Studies of transitions of care within a hospital and on discharge suggest significant communication deficits. Communication during transfers between hospitals has not been well studied. We assessed the written communication provided during interhospital transfers of emergency general surgery patients. We hypothesized that patients are transferred with incomplete documentation from referring facilities. Methods We performed a retrospective review of writte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 21 publications
0
32
0
1
Order By: Relevance
“…Prior studies indicate that documentation regarding interhospital transferred patients has been poor. [12,13] In one case, 33% of ED records missed documentation of consultation for patients who were transferred from referring EDs to a tertiary care center. [12] Furthermore, poor documentation of clinical care from referring providers resulted in more adverse events and more testing at the accepting facilities, while complete transfer documentation was associated with lower in-hospital mortality at the accepting hospitals.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Prior studies indicate that documentation regarding interhospital transferred patients has been poor. [12,13] In one case, 33% of ED records missed documentation of consultation for patients who were transferred from referring EDs to a tertiary care center. [12] Furthermore, poor documentation of clinical care from referring providers resulted in more adverse events and more testing at the accepting facilities, while complete transfer documentation was associated with lower in-hospital mortality at the accepting hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…[12,13] In one case, 33% of ED records missed documentation of consultation for patients who were transferred from referring EDs to a tertiary care center. [12] Furthermore, poor documentation of clinical care from referring providers resulted in more adverse events and more testing at the accepting facilities, while complete transfer documentation was associated with lower in-hospital mortality at the accepting hospitals. [13] Our study data showed that adequate documentation of EMTALA compliance was significantly associated with AoD patients having SBP meeting the AHA guidelines.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations